Capital Strengthening Solutions for BPR Syariah in Indonesia Case Study in the Working Area of the OJK Office of North Sumatera Province (Aceh, Sumut, Sumbar, Riau, and Kepri) - Padang, Abdul Muin Akmal; Yafiz, Muhammad; Siregar, Saparuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this research is to obtain alternative solutions for strengthening the capital of BPR Syariah in Indonesia, especially in the working area of ​​the OJK Office of North Sumatra Province, including the priority of capital problems with the Analytic Network Process (ANP) method approach. The methodology used in this research is qualitative using a questionnaire to obtain values ​​or views represented by experts, Islamic banking practitioners, and regulators in the working area of ​​the OJK Office of North Sumatra Province. The results showed that the capital problems of Islamic BPR were Fulfillment of Minimum Core Capital with an average value of 0.479, Problematic BPR Syariah with an average value of 0.252, and Monopoly of Ownership with an average value of 0.161, rater agreement of 45.68%. Solutions for strengthening the capital of BPR Syariah are Mergers with an average value of 0.177, Consolidation with an average value of 0.093, Capital Build Up with an average value of 0.092, Acquisitions with an average value of 0.089, Addition of Regional BPR Capital by BPD with an average value of 0.083, Additional Tier 1 Capital with an average value of 0.077, Commercial Bank Participation with an average value of 0.069, Supervisory Intervention with an average value of 0.051, Self-Liquidation with an average value of 0.03, and Conversion to SMFI with an average value of 0.024, rater agreement of 29.16%.